Evaluation of the Suitability of ASN Functional Positions Towards Law No. 5 of 2014 Concerning State Civil Apparatus: Case Study at the Marine and Fisheries Service of the Kepulauan Riau Province - Kurmaniah, Kurmaniah; Candra, Hendra (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2024)
The career development of functional officers within the Department of Marine Affairs and Fisheries (DKP) in Kepulauan Riau Province is essential to achieving a dynamic and professional civil service system. Functional positions, which are pivotal for enhancing public service efficiency, face challenges in terms of qualifications, training access, and performance evaluations. This study aims to assess the alignment of career development practices at DKP Kepulauan Riau with Indonesia's Law No. 5 of 2014 on the State Civil Apparatus. Using a qualitative descriptive method, primary data were gathered through interviews with functional officers, while secondary data included official organizational documents. The findings reveal that while career development aligns with the legal framework, significant challenges persist. Limited budgets restrict access to essential training and competency development programs, forcing many officers to self-finance their professional growth. Additionally, the absence of a provincial-level performance evaluation team delays the appraisal process, creating obstacles in career progression. Functional officers also face issues related to uneven staff distribution across regions and a lack of systematic institutional support for training and development. These factors hinder the optimization of their roles and responsibilities. This study concludes that addressing financial constraints, establishing a localized performance appraisal team, and implementing structured training programs are critical to improving career pathways for functional officers. By aligning career development strategies with organizational needs and providing adequate institutional support, DKP Kepulauan Riau can enhance its workforce's professionalism, contributing to sustainable maritime and fisheries management in the region.